Unilateral Facilitation Does Not Raise International Labor Migration from the Philippines - David McKenzie; Emily Beam; Dean Yang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
Significant income gains from migrating from poorer to richer countries have motivated unilateral (source-country) policies facilitating labor emigration. However, their effectiveness is unknown. We conducted a large-scale randomized experiment in the Philippines testing the impact of unilaterally facilitating international labor migration. Our most intensive treatment doubled the rate of job offers but had no identifiable effect on international labor migration. Even the highest overseas job-search rate we induced (22%) falls far short of the share initially expressing interest in migrating (34%). We conclude that unilateral migration facilitation will at most induce a trickle, not a flood, of additional emigration.
Keywords: O15; F22; O15; C93; 330; International migration; passport costs; barriers to migration; unilateral migration policy; imperfect information; job-matching; field experiment; Philippines